Laboratory Testing in the Era of Direct or Non–Vitamin K Antagonist Oral Anticoagulants: A Practical Guide to Measuring Their Activity and Avoiding Diagnostic Errors - Favaloro, Emmanuel J.; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2015)
A new generation of antithrombotic agents has recently emerged. These provide direct inhibition of either thrombin (factor IIa [FIIa]) or FXa, and are increasingly replacing the classical anticoagulants (heparin and coumarins such as warfarin) in clinical practice for a variety of conditions. These agents have been designated several acronyms, including NOACs, DOACs, and TSOACs, respectively, referring to new (novel; non–vitamin K antagonist) oral anticoagulants, direct oral anticoagulants, and target-specific oral anticoagulants, and currently include dabigatran (FIIa inhibitor), and rivaroxaban, apixaban, edoxaban, and betrixaban (FXa inhibitors). The pervading mantra that NOACs do not require laboratory monitoring is countered by ongoing recognition that laboratory testing for drug effects is needed in many situations. Moreover, since these agents “do not require” laboratory monitoring, some clinicians inappropriately take this to mean that they do not affect hemostasis tests. This review aims to briefly review the laboratory studies that have evaluated the NOACs against a wide range of laboratory assays to assess utility for qualitative or quantitative measurements of these drugs, as well as interferences that may cause misdiagnosis of hemostatic defects. Point of care testing, including use of alternate samples such as urine and serum, is also under development but is not covered extensively in this review. The main aims of this article are to provide practical guidance to general laboratory testing for NOACs, as well as to help avoid diagnostic errors associated with hemostasis testing performed on samples from treated patients, as these currently comprise major challenges to hemostasis laboratories in the era of the NOACs.
Keywords: NOACs; dabigatran; rivaroxaban; apixaban; edoxaban; measurement; interference